(untitled) (Research, Society and Development, 2021)
Organic solvents are widely used in analytical determinations. Alternative methods of analysis, reduction use of toxic solvents, and use green solvents are viable alternatives to reduce environmental impact. In addition, criteria for the proper a solvent selection for a process can greatly improve the sustainability of an analysis. The objective of the research was to carry out a comparative study of solvents used in the determination total acidity number (TAN) in oil in national and international standardized methods. Colorimetric, potentiometric and thermometric methods were evaluated. A toxicity index was established according to the hazard information described in each chemical safety sheet, to assess the standardized methods. 13 standards method were evaluated: 04 national and 09 international. The results showed that the standardized methods with the highest index of environmental impact and health were potentiometric UOP 565 and thermometric ASTM D8045. The methods with the lowest indexes were the colorimetric ASTM D1093 and ABNT NBR 16430. The products classified as a health hazard were identified in 44% of the evaluated standards. We concluded that the study of international and national standardized methods showed the need to develop methods for determining Total Acidity Number in order to reduce the impact on the operator’s health and the environment. The challenge of replacing solvents in standardized methods with green products should guide the development of alternative and sustainable methods for the analysis of acidity in oil.